2017
DOI: 10.1089/dna.2016.3276
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dobesilate Prevents Diabetic Kidney Disease by Decreasing Bim and Inhibiting Apoptosis of Renal Proximal Tubular Epithelial Cells

Abstract: Apoptosis of renal proximal tubular epithelial cells (PTECs) plays a vital role in the pathogenesis and progression of diabetic kidney disease (DKD). Calcium dobesilate is a vascular protective compound used for treatment of diabetic retinopathy and chronic venous insufficiency. The aim of this study was to determine whether calcium dobesilate can protect PTECs from glucose-induced apoptosis and the potential mechanism of this effect. It is indicated that high glucose promoted abnormal apoptosis of HK2 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…HK-2 cells, a proximal tubule epithelial cell line, were purchased from PriCells (Wuhan, China) and cultured as described previously (Cai et al, 2017). The cells were incubated in media containing 5.5 mM D -glucose + 24.5 mM D -mannitol (MG), 30 mM D -glucose (HG), or 30 mM D -glucose + 100 μM SAL (HG + SAL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HK-2 cells, a proximal tubule epithelial cell line, were purchased from PriCells (Wuhan, China) and cultured as described previously (Cai et al, 2017). The cells were incubated in media containing 5.5 mM D -glucose + 24.5 mM D -mannitol (MG), 30 mM D -glucose (HG), or 30 mM D -glucose + 100 μM SAL (HG + SAL).…”
Section: Methodsmentioning
confidence: 99%
“…HK-2 cells were stimulated with different media for 48 h, and then RNA isolation and cDNA synthesis were performed as previously described (Cai et al, 2017). Gene expression was measured by real-time polymerase chain reaction (PCR) using 0.2 μM gene-specific primers and the UltraSYBR One Step RT-qPCR kit (low ROX) (Takara Bio, Inc., Otsu, Japan) in a total volume of 20 μL.…”
Section: Methodsmentioning
confidence: 99%
“…This study also showed that Hyp could improve the function of pancreatic islets, increase glycolysis, and decrease gluconeogenesis. Regarding to diabetes-related complications, the protective effects of Hyp had been shown on diabetic nephropathy at early stage in a STZ induced-diabetic mouse model (Cai et al, 2017). Our previous results showed that Hyp could reduce the damage of isolated rat retinal vascular endothelial cells (RVECs) induced by H 2 O 2 (Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, anti-vascular endothelial growth factor (VEGF) reagents and corticosteroids are broadly used in the clinic for treating this disease (Singer et al, 2016). Calcium dobesilate, which is an established vasoactive and angioprotective drug, has been used to treat diabetic retinopathy at the systematic and local ocular level with promising results (Haritoglou et al, 2009;Cai et al, 2017). However, these drugs may show some side effects, and not all patients respond to anti-VEGF agents.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis has been found in proximal renal tubules and distal renal tubules in diabetic patients [ 9 ]. In addition, DKD animals and proximal renal tubular cells in vitro undergo apoptosis in a high-glucose (HG) environment [ 10 , 11 ]. From this evidence, we can consider the apoptosis of tubular cells to be a vital feature of DKD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%